Pengaruh Pemberian Audiovisual dan Game Puzzle terhadap Perbedaan Tingkat Kecemasan pada Anak Pra Sirkumsisi di Pondok Khitan Dusun Bancang - Minan Nur Rohman; Mokhamad Nurhadi; Nurus Safa’ah; Suhartono Suhartono (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Anxiety is an emotional response that children often experience when facing medical procedures, including circumcision. Unresolved anxiety can have a negative impact, such as increasing pain, disrupting the process of action, and causing trauma. Non-pharmacological efforts such as audiovisual administration and puzzle game therapy can be used to reduce anxiety. This study aims to analyze the difference in anxiety levels in pre-circumcision children between audiovisual giving and puzzle games at Pondok Khitan, Bancang Village, Tahulu Village. Research design using quantitative with post test design only design. The research population is pre-circumcision children at Pondok Khitan, Bancang Hamlet, Tahulu Village with a sample of 40 respondents taken with the purposive sampling technique. Consists of 20 children of the Audiovisual group and 20 children of the Puzzle Game Group. The research instrument is in the form of a child anxiety questionnaire. The research results were analyzed using the Mann-Whitney test with a significance level of α = <0,05 with an Asymp value. Sig. (2-tailed) = 0.029 < 0.05. the mean rank value of the Audiovisual group of 24.23 and the Puzzle Game group of 16.77 shows that the Puzzle Game is more effective in minimizing anxiety in pre-circumcision children which means H1 is accepted. The discovery of meaningful differences between Audiovisual and Puzzle Games towards anxiety so that the technique can be used as an interactive educational medium.